Observation of the decay B̄0→Λc+p̄π0 - Aubert, B; Karyotakis, Y; Lees, J; Poireau, V; Prencipe, E; Prudent, X; Tisserand, V; Garra Tico, J; Grauges, E; Martinelli, M; Palano, A; Pappagallo, M; et al. (2010)
In a sample of 467×106 BB̄ pairs collected with the BABAR detector at the PEP-II collider at SLAC we have observed the decay B̄0→Λc+p̄π0 and measured the branching fraction to be (1.94±0.17±0.14±0.50)×10-4, where the uncertainties are statistical, systematic, and the uncertainty on the Λc+→pK-π+ branching fraction, respectively. We determine an upper limit of 1.5×10-6 at 90% C.L. for the product branching fraction B(B̄0→Σc+(2455)p̄) ×B(Λc+→pK-π+). Furthermore, we observe an enhancement at the threshold of the invariant mass of the baryon-antibaryon pair. © 2010 The American Physical Society.